2023
DOI: 10.1097/md.0000000000035543
|View full text |Cite
|
Sign up to set email alerts
|

How readable and quality are online patient education materials about Helicobacter pylori?: Assessment of the readability, quality and reliability

Sevgi Yilmaz Hanci

Abstract: This study aimed to examine the readability, reliability, quality, and content of patient education materials (PEM) on the Internet about “Helicobacter pylori (H pylori).” A search was conducted on March 14, 2023, using the keyword “H pylori” in the Google search engine. The readability of PEMs was assessed using the Flesch reading ease score, FKGL, simple measure of gobbledygook, and gunning fog readability formulas. The reliability and quality of the websites were determined using the Journal of American Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(171 reference statements)
1
0
0
Order By: Relevance
“…It is reported that simpler words should be used instead of complicated medical terms. [ 23 – 25 , 28 31 ] When patient education materials on different subjects were examined in previous studies, it was found that their readability levels were above the recommendations, similar to our study. [ 23 – 25 , 28 31 ]…”
Section: Discussionsupporting
confidence: 88%
“…It is reported that simpler words should be used instead of complicated medical terms. [ 23 – 25 , 28 31 ] When patient education materials on different subjects were examined in previous studies, it was found that their readability levels were above the recommendations, similar to our study. [ 23 – 25 , 28 31 ]…”
Section: Discussionsupporting
confidence: 88%